"Giving yourself some breathing room…": an exploration of group meditation for people with aphasia. Issue 12 (2nd December 2021) - Panda, Sweta; Whitworth, Anne; Hersh, Deborah; Biedermann, Britta
ABSTRACT: Background: Meditation practices have been found to improve both cognitive and psychological functions related, in particular, to attention and well-being in both healthy people and those with chronic health conditions, including stroke. Considering the range of cognitive and psychosocial consequences in people with post-stroke aphasia, meditation has been identified as a potential rehabilitative tool to target these areas, investigating also, in some studies, any potential impact on language abilities. Even with growing numbers of studies exploring the effectiveness of meditation techniques in the stroke population, no study to date has sought to explore the impact of meditation from the perspective of the lived experience of people with aphasia. Aim: This preliminary study explored the perceived impact of meditation on a range of activities and areas of participation for people with chronic aphasia who, with the exception of one participant, learned how to meditate after the onset of their stroke. Methods: Five participants who regularly attended a meditation group for people with aphasia agreed to an individual semi-structured interview, followed by participation in two subsequent focus groups to member-check data. Interviews were thematically analysed using an Interpretative Phenomenological Analysis approach in order to capture the lived experience of meditation. Results: A consistent and positive psychosocial impact was reported by all participants related to the development of acceptance and resilience post-stroke. As with healthy meditators, individual variation was seen in how people learn meditation, and in their preferences and success with different meditation techniques. The reduced focus on the language impairment itself was a strong motivator to attend the meditation group; however, the benefit of regular practice on self-acceptance and building resilience, and a sense of calm, were also prominent themes. The positive experience of meditating in a group was a further motivator to participate regularly in the meditation practice. Conclusion: Meditation can have psychosocial benefits for people with aphasia and may offer a positive and complementary approach when living with aphasia following stroke. Individual variation in responsiveness to meditation techniques highlighted the importance of monitoring participant preferences when delivering and interpreting meditation outcomes with people with aphasia. The role of meditation in language rehabilitation with people with chronic aphasia as a complementary treatment tool remains an area of future enquiry.